Online English Vocabulary Teaching Using Kahoot! for Students with Special Needs - Anandha Anandha; Dini Anggraheni; Adiprana Yogatama (Scripta : English Department Journal, 2020)
The purpose of this research is to increase the English vocabulary of students with special needs. One of the online learning platforms use in this research is Kahoot!. The research subjects were SLB D YPAC Semarangstudents who were members of the Y-EClub Semarang. The research method used descriptive qualitative. The results of the research are the members of Y-Eclub SLB D YPAC Semarang using Kahoot! in learn English. They were able to catch the English vocabulary. Conclusion of this research is that Kahoot! as the internet-based platform is an effective medium in English teaching so that students could memorize English Vocabulary.